Spectral-domain optical coherence tomography characteristics of cystic retinal tuft - Haidong Li; Lifeng Chen; Meng’ai Wu; Bin Zheng (BMC Ophthalmology, 2022)
Abstract Objective To investigate the characteristics of cystic retinal tufts (CRTs) with 55° widefield spectral-domain optical coherence tomography. Methods This was a retrospective study. All subjects underwent a complete ocular examination, ultra-widefield (UWF) pseudocolor fundus photography and Spectral domain optical coherence tomography (SD-OCT) with a 55° widefield lens. The SD-OCT characteristics were analyzed in subjects with CRT. Results Twenty-six eyes of 25 subjects were scanned and 29 CRTs were analyzed for SD-OCT characteristics. On SD-OCT images, the CRTs exhibited hyperreflective irregular elevated lesions with internal hyporeflective cystoid cavities. Normal layers of the neuroepithelium could not be distinguished. The mean diameter of CRTs was 1022 microns (range, 117–3711 microns; standard deviation, 815 microns). There was vitreoretinal traction at the apex of CRTs. Among them, retinal tears in 24.14% (7/29), suspected retinal tears in 27.59% (8/29), and shallow neuroepithelium detachment in 31.03% (9/29). Conclusions The widefield SD-OCT imaging can provide detailed cross-sectional anatomic information of CRT and may guide clinical treatment.